PEMBELAJARAN MENULIS TEKS NEGOSIASI DENGAN MENGGUNAKAN METODE THINK PAIR SHARE DI KELAS X - Imas Umayah; Putri Bunga Annisa; Diena San Fauziya (IKIP Siliwangi, 2019)
This research is backed by the curiosity of researchers about the influence of the TPS learning method in the text of negotiation in class X. The focus of this research is finding out if there are differences in the learning outcomes of text. Negotiations before and after treatment. This research aims to determine the influence of use of TPS methods against negotiating text skills using experimental methods. Based on the results of the research in class X before using the TPS method The value of students has an average is 54 whereas after using the method has an average of 67 which means posttest is better than pretest. Learning to write negotiation text using the TPS method runs effectively as evidenced by the increase between the value before and after the application of the method. Wilxocon test Results sig value 0,000 < 0.05. Then there is a noticeable difference in the negotiation text seen from the pretests and posttest data. Thus, the TPS method is effective if used in learning to write negotiation text.